2013
DOI: 10.1016/j.ijcard.2012.01.080
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of coronary stent thrombosis: Evidence from an international collaborative meta-analysis including 30 studies, 221,066 patients, and 4276 thromboses

Abstract: Despite numerous possible risk factors, the most common and consistent predictors of stent thrombosis are early antiplatelet therapy discontinuation, extent of coronary disease, and stent number/length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
2
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 168 publications
(103 citation statements)
references
References 95 publications
7
92
2
2
Order By: Relevance
“…ST occurred more frequently in the subgroup of patients without postdilatation. ST represents an important issue in the ACS setting as it is potentially triggered by enhanced aggregation of platelets [34]. BRS represents a potential risk for scaffold thrombosis because of the relatively thick struts and limited expansion.…”
Section: Discussionmentioning
confidence: 99%
“…ST occurred more frequently in the subgroup of patients without postdilatation. ST represents an important issue in the ACS setting as it is potentially triggered by enhanced aggregation of platelets [34]. BRS represents a potential risk for scaffold thrombosis because of the relatively thick struts and limited expansion.…”
Section: Discussionmentioning
confidence: 99%
“…3 A meta-analysis found that the risk of stent thrombosis was highest in the setting of extensive CAD, early discontinuation of DAPT, and number of stents 4 with these risk factors alone, the patient was already at higher risk for a negative outcome.…”
Section: "There Is No Disease More Conducive To Clinical Humility Thamentioning
confidence: 99%
“…The choice of antiplatelet agents and duration of antiplatelet therapy after ACS may be influenced by the presence of risk factors for stent thrombosis [28] and the type of management used (medical treatment with or without delayed angiography, acute or emergent PCI, CABG) [29,30].…”
Section: Indications and Guidelines On Myocardial Revascularizationmentioning
confidence: 99%